Nurturing an aesthetic tribe: Consuming and (re)producing 'Quarantine Art'. (June 2023) - Hietala, Iida
This article explores 'quarantine art' – an Instagram challenge of recreating well-known artworks in self-isolation for the consumption of others – to investigate how people come together on social media to form an aesthetic tribe of consumer-producers. Drawing on a mixed-method qualitative approach, it presents netnographic observations and participant interviews subjected to representational and non-representational analyses. The findings illuminate the broad assemblage of visual arts, crafty practices and social media affordances that allow for a new communal expression, an aesthetic form of being together, and an emancipatory embrace of the ancient 'maternal' trope. That is, a new type of female subjectivity is brought to the fore – one that, separated from its ancient predecessors burdened by 'caring for others', celebrates aesthetic expression, nurturing and caretaking as a means to break down isolation. Overall, this study offers a feminist post-postmodern reading and elaboration of research into consumer tribes and virtual communities gathered around art, culture and aesthetics.